The Implications of Husbands as Donors on Wife's Psychology (An Islamic Family Law Review of the Al Qolam Foundation) - Anisa Diah Fitriani; Witia Oktaviani (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2026)
Philanthropic activities shadaqah are highly recommended in Islam as a form of worship. However, when husbands prioritize donations without considering the stability of household finances, it can create a dissonance between socio-religious responsibilities and domestic obligations. This situation has the potential to cause emotional discomfort and psychological burdens on wives. This study aims to analyze the practice of donations made by husbands to the Al Qolam Foundation, examine its psychological implications for their wives, and review this phenomenon from the perspective of Islamic family law. Unlike previous studies that predominantly highlight the positive impacts and altruistic factors of general philanthropy, this research offers a novel perspective by critically examining the intersection of philanthropic zeal and internal family dynamics, specifically uncovering the potential psychological detriment to wives when sunnah (voluntary) donations conflict with obligatory nafkah (financial maintenance). This research utilizes a qualitative method with a case study approach. It is a normative-empirical legal study. Primary data was collected through structured interviews with husbands acting as donors at the foundation and their wives, while secondary data was gathered through relevant literature studies. The findings reveal that the husbands' donation activities are primarily driven by religious motivations, the desire to support children's Islamic education, and social solidarity (ta'awun). Despite these noble intentions, the donations often negatively impact the wives' psychological well-being, manifesting as stress from household financial decline, a perceived lack of attention, and feelings of resentment. Based on Islamic family law, providing nafkah is an absolute legal obligation that must be prioritized over voluntary donations. Donating under unstable financial conditions that neglects family rights and causes psychological distress to the wife is unjustified. Such practices contradict the fundamental Islamic legal maxims of al-wajibu muqaddam 'ala sunnah and laa dharara wala dhirara.